Status, socio-ecological drivers and management implications of free-grazing livestock in Vietnam’s special-use forests - Dong Thanh Hai,; Ha Van Nghia,; Nguyen Manh Hiep, (Journal of Forestry Science and Technology, 2025)
Livestock grazing in Vietnam’s special-use forest (SUF) system is both a social and ecological issue, reflecting the dependence of buffer-zone communities on forest resources while posing a challenge to biodiversity conservation. This study, conducted across 46 SUFs representing major ecological regions, combined quantitative and qualitative approaches to assess current grazing status, socio-ecological drivers, and management implications. Results revealed that 78.3% of SUFs had livestock grazing, with an average herd size of 45,486 ± 2,350 animals, of which 85.7% were free-ranging. Muong Nhe Nature Reserve was identified as a hotspot with 18,305 animals. The density of forest protection staff averaged 0.9 ± 0.4 persons per 1,000 ha—below the IUCN recommendation of about 2 persons per 1,000 ha—indicating limited human resources and management capacity. Regression analysis showed a strong correlation between herd size and the number of conservation violations (r = 0.985; R² = 0.97; p < 0.01), confirming herd size as a reliable indicator of ecological pressure. Qualitative analysis identified five key drivers: land scarcity, traditional practices, livelihood dependence, inadequate budgets, and weak coordination. The study proposes four management strategies: (i) strengthening institutional capacity and ecological monitoring technology; (ii) promoting co-management mechanisms; (iii) spatial planning for controlled grazing and alternative livelihoods; and (iv) integrating a One Health approach into conservation policies. The findings provide national-level empirical evidence on the socio-ecological mechanisms of livestock grazing, supporting adaptive management and sustainable development in buffer-zone communities.